Spontaneous Triplet Pregnancy - A Case Report (Journal of Dhaka Medical College, 2010)
A patient age 25 years para 1, 2nd gravida with previous history of Caesarean Section (delivered a still born baby due to APH) was admitted into DMCH with 33weeks pregnancy and back pain for 5 days. She was not in regular antenatal check up but completed immunization against tetanus. She was a regularly menstruating woman. She noticed undue enlargement of abdomen in her last trimester with excessive fetal movement. On examination, her BP was found 100/70 mmHg, with bilateral leg oedema. SFH was 36wks size & fetal heart sound was audible at multiple sites. Her USG shows triplet live pregnancy of 33-34 weeks duration. Elective C\S was done after 2 weeks at 06.04.2010. Three live birth premature babies were delivered. Weight of the babies was 2.1kg, 2kg, 1.9kg. After 7 days of hospital stay, the patient was discharged with three healthy kids and great pleasure. Key words: Triplet pregnancy; Ceasarean section. DOI: 10.3329/jdmc.v18i1.6314 J Dhaka Med Coll. 2009; 18(1) : 88-90